Plague and Violence in Early Modern Italy. (20th November 2018) - Rose, Colin
Abstract: Following the plague of 1630, which struck Northern Italy particularly hard, the erosion of social norms and hierarchies led to an outbreak of homicidal violence in the city and province of Bologna. In particular, urban nobility resumed practices of vendetta and revenge as politics that had lain dormant for some decades; while in the countryside, the heightened stresses of endemic rural poverty led to homicides over resources such as land, food, and employment. This article examines that outbreak of violence in the context of natural disaster, employing a selection of seventy-seven homicide trials prosecuted by the Tribunale del Torrone, the criminal court of Bologna, in 1632.